(untitled) (Biological Sciences - PJSIR, 1999)
HMCis playing vital role in country-wide proliferation of the technology.It is involved in designing and manufacturing of various plants and heavy machinery. Cranes are also included in the HMC manifold. This paper explains the methodology of converting the conventional design process of overhead cranes to Computer Aided Design (CAD), software engineering approach and the usage of different tools in order to get a computer based solution for the design of overhead cranes. Applications of parametric design and design for manufacturing concepts may also be seen. The main idea is to automate the drafting process by linking it to design and analysis phase.